2006
DOI: 10.1016/j.neuroscience.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in parvalbumin, but not in calbindin D-28k upregulates mitochondrial volume and decreases smooth endoplasmic reticulum surface selectively in a peripheral, subplasmalemmal region in the soma of Purkinje cells

Abstract: Abstract-The Ca 2؉ -binding proteins parvalbumin (PV) and calbindin D-28k (CB) are key players in the intracellular Ca 2؉ -buffering in specific cells including neurons and have profound effectson spatiotemporal aspects of Ca 2؉ transients. The previously observed increase in mitochondrial volume density in fast-twitch muscle of PV؊/؊ mice is viewed as a specific compensation mechanism to maintain Ca 2؉ homeostasis. Since cerebellar Purkinje cells (PC) are characterized by high expression levels of the Ca 2؉ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 63 publications
6
43
1
Order By: Relevance
“…Prior experiments in cerebellar Purkinje cells indicated that deficits in CB and PV resulted in increased neuronal spine length and volume in these cells (Vecellio et al, 2000;Chen et al, 2006). Although we did not find any changes in the actual number of PV ϩ or CB ϩ neurons in response to RRS, it interesting to note that these two populations displayed the most profound deficits in c-Fos expression.…”
Section: Consequences Of Rrs-mediated Decreases In C-fos Expressioncontrasting
confidence: 61%
“…Prior experiments in cerebellar Purkinje cells indicated that deficits in CB and PV resulted in increased neuronal spine length and volume in these cells (Vecellio et al, 2000;Chen et al, 2006). Although we did not find any changes in the actual number of PV ϩ or CB ϩ neurons in response to RRS, it interesting to note that these two populations displayed the most profound deficits in c-Fos expression.…”
Section: Consequences Of Rrs-mediated Decreases In C-fos Expressioncontrasting
confidence: 61%
“…The most striking alterations in the absence of PVare the morphological changes observed in the soma. The volume of mitochondria, Ca 2þ sequestrating organelles that also serve as transient Ca 2þ stores (Billups and Forsythe 2002;Murchison and Griffith 2000), is increased by about 40% selectively in a narrow compartment underneath the plasma membrane (Chen et al 2006). Concomitantly, the subplasmalemmal smooth ER compartment is decreased (Fig.…”
Section: The Ca 2þ Homeostasomementioning
confidence: 99%
“…One argument is the generality of the mechanism and a second one the reciprocality as exemplified for the relationship between PV content and mitochondrial volume. In the absence of PV in PV 2/2 mice, an up-regulation of mitochondria occurs not only in PV-ergic Purkinje cells (Chen et al 2006) or cerebellar stellate and basket cells (B Schwaller, unpubl. ), but is also seen in PV 2/2 fast-twitch muscle fibers (Chen et al 2001).…”
Section: Cytosolic Ca 2þ Buffersmentioning
confidence: 99%
“…Protein samples were separated by SDS-PAGE (12.5%) and transferred onto nitrocellulose membrane using semi-dry blotting apparatus (Bio-Rad). Membranes were stained with Ponceau S to check for even loading of the gels and then further processed as described before (Chen et al, 2006) using total-Akt antibody (1:1000, Cell Signaling Technology) and phospho-Akt antibody (1:1000, Ser 473, Cell Signaling Technology).…”
Section: Western Blotmentioning
confidence: 99%